ZepQuiz Game-Based Learning for Improving Students’ Narrative Reading Skills: ZepQuiz: Pembelajaran Berbasis Permainan untuk Meningkatkan Keterampilan Membaca Naratif Siswa - Dian Rahma Santoso; Pasya Rahma Tamara; Calista Ananda Nabhila; Andini Widia Ningsih; Gita Desire Sujarwo; Nurul Lailatul Qodriatil Fadlilah (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Reading comprehension remains a core challenge in English as a Foreign Language (EFL) learning. Specific background: Many high school students struggle to understand narrative text structures and implicit meanings. Knowledge gap: Few studies have investigated the integration of the ZepQuiz platform within Game-Based Learning (GBL) to enhance narrative reading comprehension at the secondary level. Aims: This study examined the use of ZepQuiz as a digital learning medium to improve students’ reading comprehension and motivation in narrative texts. Results: Using a one-group pretest-posttest quantitative design, findings from 35 students showed a statistically significant improvement (p < 0.05) in reading comprehension and motivation scores after ZepQuiz implementation. Novelty: The research highlights ZepQuiz’s ability to integrate gamification elements—leaderboards, instant feedback, and time challenges—to promote engagement and cognitive processing. Implications: ZepQuiz can be applied as an innovative and interactive learning approach to support digital-based English education. Highlight & Keyword• Motivation improvement through gamified reading• Cognitive engagement in narrative comprehension• Technology-based EFL instruction Keywords: ZepQuiz, Game-Based Learning, Reading Comprehension,Narrative Text, English Education